Technical Evaluation of Solar Power Pack Efficiency for Mini AIS ( Automatic Identification System) on Traditional Tourist Vessels - Jangka Rulianto; Arif Fahmi; Khoirul Umam; Abdur Rohman; Indra Kurniawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat - Universitas Abdurachman Saleh Situbondo, 2026)
Traditional tourist vessels play a crucial role in supporting the marine tourism sector, particularly in the coastal areas of Banyuwangi. However, limitations in energy supply and the lack of remote monitoring systems often pose challenges to service quality and vessel safety. This community service initiative aims to enhance the service quality and safety of tourist boats through the implementation of a solar-powered pack system based on Internet of Things (IoT) technology and a Long Range (LoRa) network on vessels managed by the POKMASWAS Pesona Bahari group. The implementation methodology includes stages of education, technical training, assembly of the solar power pack system, installation of IoT sensors, and integration of a LoRa network for real-time data monitoring. The results demonstrate an improvement in the knowledge and technical skills of POKMASWAS members in operating the technological devices, alongside the establishment of an independent electrical system and a remote monitoring capability that can accelerate emergency response. The implementation of this technology provenly supports the operational sustainability of traditional tourist vessels, while strengthening the capacity of coastal communities in managing tourism in a safer, more modern, and environmentally friendly manner.